Optimizing academic supervision through CoMent strategy in STEAM-ED approach and application of fractal geometry - Rahmad Ramelan Setia Budi; Rambat Nur Sasongko; Badeni Badeni; Muhammad Kristiawan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
This study examines the implementation of academic supervision using the CoMent Strategy of school supervisors in an effort to maximize the STEAM-ED approach and the application of fractal geometry to Batik and Textile Creative Craft instructors at State Vocational School 5 Bengkulu City. The method used was qualitative descriptive method. This research was conducted over two academic years in the academic year 2019-2020 to 2020-2021.  In this study, the subjects studied were teachers in the competence of Batik & Textile Creative Crafts, totaling 8 people. The data collection in this study used testimonials in the form of learning logs and documentation. The data analysis was an interactive model of data analysis technique. The results showed that there is a high level of satisfaction in carrying out the learning process using the STEAM-ED approach and the application of fractal geometry, as well as the performance of the trained teachers. The adoption of academic supervision through the CoMent technique proved to be highly effective in maximizing the STEAM-ED approach and the use of fractal geometry for Batik and Textile Creative Craft instructors in their learning. The advantage of the Coment strategy is that it can streamline the implementation of academic supervision of fostered teachers in an effort to provide active, effective, meaningful and fun learning for each student so that they are able to think critically, be creative, innovate, have higher order thinking skills and be creative in solving problems through coaching and mentoring assistance activities.